Potential contribution of genomics and biotechnology in animal production - Casas, Eduardo; Montaldo, Hugo H.; Nonneman, Dan J.; Poli, Mario Andres (Biblioteca Básica de Agricultura, 2022)
Integration of Latin American countries into international agricultural markets requires animal production systems to be competitive. Demand of animal products is increasing due to population growth, and changes in lifestyle of some countries. This will demand modifications to the production systems to increase efficiency of animal production. The use of genomics will offer new opportunities to improve animal production that is sustainable and highly competitive in world markets.